Looking for the hidden mutation: Bannayan–Riley–Ruvalcaba syndrome caused by constitutional and mosaic 10q23 microdeletions involving PTEN and BMPR1A. Issue 7 (6th May 2019) - Golas, Monika M.; Auber, Bernd; Ripperger, Tim; Pabst, Brigitte; Schmidt, Gunnar; Morlot, Michel; Diebold, Uta; Steinemann, Doris; Schlegelberger, Brigitte; Morlot, Susanne
Abstract: The PTEN hamartoma tumor syndrome (PHTS) is caused by heterozygous germline variants in PTEN . Here, we report two unrelated patients with juvenile polyposis, macrocephaly, intellectual disability, and hyperpigmented skin macules. Both patients were clinically suspected for the Bannayan–Riley–Ruvalcaba syndrome (BRRS), a PHTS subentity. By array‐CGH analysis, we identified an interstitial 10q23.1q23.3 deletion in a buccal mucosa sample of Patient 1 that encompassed PTEN, BMPR1A, and KLLN, among others. In contrast, neither sequencing nor array‐CGH analysis identified a pathogenic variant in PTEN or BMPR1A in a blood sample of Patient 2. However, in a surgical specimen of the thyroid gland high‐level mosaicism for a 10q23.2q23.3 deletion was observed. Additionally, the pathogenic PTEN variant c.956_959delCTTT p.(Thr319LysfsTer24) was detected in his thyroid tissue. The frame shift variant was neither detected in the patient's blood nor in his buccal mucosa sample. Low‐level mosaicism for the microdeletion was identified in a buccal swap sample, and reanalysis of the blood sample suggested marginal‐level mosaicism for deletion. The 10q23.2q23.3 deletion mosaicism was also identified in a subsequently resected colonic polyp. Thus, in both cases, the diagnosis of a 10q23 deletion syndrome, which clinically presented as BRRS, was established. Overall, the study expands the BRRS spectrum and highlights the relevance of considering mosaicism in PHTS. We conclude that in all patients with a clear clinical suspicion of PHTS, in which genetic analyses of DNA from blood and buccal swap samples fail to identify causative genetic variants, genetic analyses of additional tissues are recommended.